Food Sensory Properties and the Older Adult. Issue 4 (1st June 2016) - Field, Katherine; Duizer, Lisa M.
Abstract: Older adults represent a large and growing portion of the global population. Given the high risk of malnutrition in this population, it is important to understand factors influencing food intake; sensory perception is one of these factors. Aging is associated with a number of physiological changes that alter the way food sensory properties are perceived. Because of these changes, it is often assumed that older adults experience a decrease in food liking. Although there is little evidence to support this assumption, many studies have evaluated flavor enhancement strategies aiming to increase food liking in older adults. As older adults exhibit a high degree of heterogeneity in their liking response, more tailored approaches may be required to increase food liking in older adult populations. Current attempts to classify subgroups of older adults have had little success. Furthermore, consideration should be given to food texture in future studies, as it plays a dominant and increasingly vital role in food perception by older adults. Practical Applications: Sensory perception plays an important role in food choice and intake, thus it is important to understand how foods are perceived by older adults. This is essential to the health and well‐being of older adults, as the reduction in food intake often observed with ageing is a key contributor to malnutrition in this population. The success of studies aiming to improve food liking in older adults have had very limited success to date, with some strategies actually leadings to a reduction in food consumption. To improve the success of future strategies, food perception by older adults, and the increasingly vital role of food texture must be understood.